2019
DOI: 10.1002/cjce.23588
|View full text |Cite
|
Sign up to set email alerts
|

Graphene functionalized decellularized scaffold promotes skin cell proliferation

Abstract: An increasing number of new strategies for skin tissue engineering have been developed with the potential to mimic the biological properties of native tissue with a high degree of complexity, flexibility, and reproducibility. In this study, decellularized tissue (DT) was prepared from the bovine heart by using chemical treatments. However, the mechanical properties of the DT constructs were poorer than the extra cellular matrix of the skin tissue. To overcome this challenge, hybrid scaffolds of DT and graphene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Jafarkhani and colleagues obtained a decellularized scaffold from a bovine heart; the cell-free prototype was also functionalized with graphene oxide (GO) and engineered with skin cell lines (NIH/swiss mouse embryo fibroblast cells, NIH 3T3). The in vitro results proved the capability of the prototype scaffold to form a microenvironment for cell proliferation, differentiation, migration and gene expression and the authors demonstrated its applicability and suitability as a support material for tissue engineering [ 110 ].…”
Section: Scaffolds For Skin Tissue Engineering and Cutting-edge Tementioning
confidence: 99%
“…Jafarkhani and colleagues obtained a decellularized scaffold from a bovine heart; the cell-free prototype was also functionalized with graphene oxide (GO) and engineered with skin cell lines (NIH/swiss mouse embryo fibroblast cells, NIH 3T3). The in vitro results proved the capability of the prototype scaffold to form a microenvironment for cell proliferation, differentiation, migration and gene expression and the authors demonstrated its applicability and suitability as a support material for tissue engineering [ 110 ].…”
Section: Scaffolds For Skin Tissue Engineering and Cutting-edge Tementioning
confidence: 99%
“…Many new tissue engineering strategies have been proposed that largely imitate the biological properties of body tissues that are very complex and reproducible. Hybrid scaffolds of decellularized tissue (DT) and GO were presented in [85]. The GO concentration effects on the physical, chemical, and structural characteristics, such as the porosity, pore size, morphology, mechanical strength, and capacity of water uptake, have been tested.…”
Section: Nanotheranostics and Tissue Engineeringmentioning
confidence: 99%
“…Compared to the DT scaffolds, the scaffold containing 3% GO showed a mechanical strength and cell viability increase of about 25%. This porous scaffold promoted cellular activity and cell adhesion and proliferation using a biomimetic construction suitable for clinical applications [85].…”
Section: Nanotheranostics and Tissue Engineeringmentioning
confidence: 99%
“…(E) Porous structure of bovine cardiac ECM-GO functionalized scaffold. Cell viability vs. GO content (Jafarkhani et al, 2020 ). (F) Decellularized (+Dcell) and non-decellularized (–Dcell) jellyfish bell scaffolds.…”
Section: Recent Progress In Scaffolds For Skin and Brain Tissue Engineeringmentioning
confidence: 99%
“…Another strategy for skin TE is to augment the cell viability by using decellularized tissue with retained primary ECM constituents. ECM-based materials can be sourced from different organs, such as small bovine intestine (Parmaksiz et al, 2019 ) and bovine cardiac tissue (Jafarkhani et al, 2020 ). Functionalized freeze-dried scaffolds consisting of bovine cardiac ECM-based graphene oxide (GO) have demonstrated better mechanical properties and cell viability than decellularized tissue scaffolds ( Figure 7E ) (Jafarkhani et al, 2020 ).…”
Section: Recent Progress In Scaffolds For Skin and Brain Tissue Engineeringmentioning
confidence: 99%